2011
DOI: 10.1371/journal.pone.0018902
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of RND Efflux Transporters in Burkholderia cenocepacia

Abstract: Burkholderia cenocepacia J2315 is representative of a highly problematic group of cystic fibrosis (CF) pathogens. Eradication of B. cenocepacia is very difficult with the antimicrobial therapy being ineffective due to its high resistance to clinically relevant antimicrobial agents and disinfectants. RND (Resistance-Nodulation-Cell Division) efflux pumps are known to be among the mediators of multidrug resistance in Gram-negative bacteria. Since the significance of the 16 RND efflux systems present in B. cenoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 45 publications
7
63
0
Order By: Relevance
“…Previous data revealed that RND-4 efflux pump is involved in the extrusion of different toxic compounds, including some antibiotics. Moreover, in our recent paper, transcriptomic and phenomic analyses suggested that the deletion of RND-4 coding genes might have a "pleiotropic" effect in the B. cenocepacia J2315 metabolism [14]. These findings were in part confirmed by the proteomic analysis performed in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Previous data revealed that RND-4 efflux pump is involved in the extrusion of different toxic compounds, including some antibiotics. Moreover, in our recent paper, transcriptomic and phenomic analyses suggested that the deletion of RND-4 coding genes might have a "pleiotropic" effect in the B. cenocepacia J2315 metabolism [14]. These findings were in part confirmed by the proteomic analysis performed in this study.…”
Section: Discussionsupporting
confidence: 82%
“…cepacia complex bacteria are traditionally considered to be intrinsically resistant to aminoglycosides through a number of different resistance mechanisms, including the resistancenodulation-division (RND) efflux systems (14). Confirming this fact, in our series of experiments, we found a near-complete absence of effect of tobramycin at a concentration of 8 g/ml (representing systemic drug concentrations) on biofilm thickness and viability.…”
Section: Discussionsupporting
confidence: 77%
“…RNDs 6 and 7 are twin pumps encoded by the same operon, similar to MdtBC of E. coli (127,611). Inactivation of the rnd-4 gene led to a 4-to 8-fold increase in susceptibility to aztreonam, ciprofloxacin, levofloxacin, gentamicin, tobramycin, and chloramphenicol (614,615). With 16 RND pumps present in B. cenocepacia strain J2315, their differential roles in drug resistance of planktonic and biofilm cells were investigated (613).…”
Section: Burkholderia Sppmentioning
confidence: 99%
“…Upregulation of multiple proteins, including an uncharacterized RND pump and the OmpA and CarO OM proteins, also occurs in A. baumannii biofilms (894). However, despite the overall positive impact of drug exporters on biofilm formation, the inactivation of two RND pumps (i.e., RND-4, RND-9, or both) in a B. cenocepacia strain enhanced biofilm formation (615). These observations of the efflux pump's impact on biofilm formation may partially be attributable to the altered levels of certain signaling molecules in the mutant strains.…”
Section: Role Of Efflux Pumps In Biofilm Formation and Resistancementioning
confidence: 99%